Coupled heat and mass transfer by MHD natural convection of micropolar fluid about a truncated cone in the presence of radiation and chemical reaction (Journal of Naval Architecture and Marine Engineering, 2013)
An analysis is performed to study the thermal radiation and chemical reaction effects on coupled heat and mass transfer by MHD natural convective boundary-layer flow of a micropolar fluid over a permeable truncated cone with variable surface temperature and concentration. A suitable set of dimensionless variables is used to transform the governing equations of the problem into a non-similar form. The resulting non-similar equations have the property that they reduce to various special cases previously considered in the literature. An adequate and efficient implicit, tri-diagonal finite difference scheme is employed for the numerical solution of the obtained equations. Various comparisons with previously published work are performed and the results are found to be in excellent agreement. A representative set of numerical results for the velocity, microrotation, temperature and concentration profiles as well as the local skin-friction coefficient, local wall couple stress, local Nusselt number and the local Sherwood number is presented graphically for various parametric conditions and discussed.DOI: http://dx.doi.org/10.3329/jname.v10i2.15898